Analisis Pengaruh Karakteristik Individu Gaya Kepemimpinan Lingkungan Kerja Dan Budaya Kerja Terhadap Kinerja Pegawai Pada Dinas Perdagangan Kabupaten Alor - Jakra, Siti Saidah; Peny, Theresia Lounggina Luisa; Hermayanti, Hermayanti; Gorang, Alvonso Fanisius (Peneliti.net, 2023)
Employee performance is the result of work achieved in carrying out the tasks assigned to employees at the Alor District Trade Office. The purpose of this study was to determine the effect of individual characteristics, leadership style, work environtment and work culture on employee performance at the Alor District Trade Office. Either partially or simultaneously. This type of research is a quantitative description. Samples were taken using saturated sampling technique. The samples in this study were 34 employees. Data collection tools used are observation, interviews, questionnaires and literature studies. The data analysis model used to answer the hipotesis is multiple analysis, t test, F test. The result of this study indicate that partially and simultaneously individual characteristics, leadership style, work environtment and work culture on employee performance at the Alor District Trade Office, the partially significance value of the individual characteristics variable is 0.002, leadership style variable is 0.002, the work environtment variable is is 0.003, the work culture variable is 0.005, and simultaneously the significance value of the F test is 0.000, the result of the t test and F test are smaller than alpha (0.05), so the hipotesis testing credited in this study is as follows: there is and influence of individual characteristics, leadership style, work environtment and work culture on employee performance at the Alor District Trade Office.